Robot as Legal Person: Electronic Personhood in Robotics and Artificial Intelligence - Avila Negri, Sergio M. C. (Frontiers in Robotics and AI, 2021)
This paper seeks to investigate the proposal to create a legal (electronic) personhood for robots with artificial intelligence based on the European Parliament resolution with recommendations on Civil Law and Robotics. To this end, we highlight the various risks and problems present in this type of initiative, especially in view of the current trend of expanding legal subjectivity in various jurisdictions. In addition to an anthropomorphic rhetoric, we can observe the prevalence of a pragmatic line that seeks to be guided, mainly, by the model of corporations, without taking into account, however, problems present in the process of embodiment of companies and the particular function of the term legal person in the grammar of Law.